IMPLEMENTASI PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN PENGUASAAN KONSEP DAN KREATIVITAS SISWA PADA MATERI SEL ELEKTROLISIS - Mia Lektriani, - (2019)
The purpose of this study is to obtain information on the implementation of Project Based Learning (PjBL) to increase students' mastery of concept and creativity in sub electrolysis cell material. In the study was used quasi-experimental design with pretest posttest non equivalent control group design.; Subject of the study consisted of 20 students who received the experimental group learning PjBL model, and 20 students as a control group who used learning conventional. Research instruments used include a written test sheet mastery of concepts and creative thinking, observation sheet and questionnaire. Improved learning outcomes using the gain normalized <g>, measured include aspects of creativity to think and to act. Data analysis used The Mann-Whitney test while T test used Person Correlation test. The results showed that there are influence of model, PjBL toward student's mastery of concepts and creativity at the material of electrolysis cell. The results showed that there are influence of the PjBL model on students' mastery of concepts and creativity, signed with significant increase. The enhancement mastery of concept of experiment group in the high category, and control group in medium category. The enhancement creativity of experiment group in the medium category, and control group in low category. Correlation test shows that the mastery of concepts and creative thinking has a very strong relationship, while the mastery of concepts and creative act, and creative thinking and creative act have a very weak relationship. Most of the students responded that the application of PjBL in learning can increase their interest and motivation, so students more easily understand the concept of electrolysis and creativity of the students can be increased.